An Instructional Approach for Product Features and Customer Preference Identification Using Product Reviews - Johnson Lim, Soon Chong; Zakaria, Anies Faziehan (Engineering & Technology Research, 2017)
Product design is a rapidly growing area that utilizes various technology and innovation to meet customer needs. In design, identifying customer needs is the first step toward designing a successful product. The conventional methods of obtaining customer needs are through surveys, questionnaires, and interviews. However, in the era of rapid development of the internet, consumer nowadays have a tendency to share their product experiences online. Thus, in the design perspective, online product reviews are one of the valuable sources to obtain user requirements. This study proposes the development of an instructional kit for product features and customer preference identification using product review documents. An instructional kit was developed to obtain user preferences using ADDIE development method. Three laptop brands were chosen and a total of 60 product reviews documents were retrieved from the two selected websites. The collection of data scores was analyzed using statistical approach to identify correct tag set. For evaluation of instructional kit, ten respondents with non-engineering background were involved to examine the effectiveness of the approach. The performance grades were determined using four achievement levels, with excellent score of 67 marks and above and passing score of 43 marks. The result shows that nine out of ten respondents were categoriezed under excellent score. The findings of this study indicated the suitability and applicability of the instructional kit for analyzing user preferences using online reviews.